Web-Based Customer Relationship Management (CRM) For Graduate Studies Unit (GSU) - El Breiki, Walid A. Mohamed (2008)
Web-based system has changed the way of information worldwide and considered as a common tool to share information on the Internet. With the advent of web-based system, many organizations used it as a medium to integrate inter-enterprise application across the Internet. Moreover, web-based system as information distributor not only for business, entertainments, educations purpose, but also for a major role to play in the administration of trade, security, integrity, Student Admission System, (CRM) Customer Relationship Management System. The overall progression of the project includes problem and limit encountered during the development of this project. Now University Graduate Studies Unit (GSU) working manually. It is an important, though, to have an interactive system in place to manage feedback, control quality (and online support) and decrease the number of unhappy customers. It is hard to make each customer a happy customer. An organized and well-maintained web-based customer support system is crucial to any online adventure as it can be accessed by anyone, anywhere, anytime that added values to end users.